2018
DOI: 10.1016/j.clnesp.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of thiamine dependent enzymes in obesity and obesity related chronic disease states: A systematic review

Abstract: The WHO 2016 report indicates that worldwide obesity is rising, with over 600 million people in the obese range (BMI>30). The recommended daily calorie intake for adults is 2000 kcal and 2500 kcal for women and men respectively. The average American consumes 3770 kcal/day and the average person in the UK consumes 3400 kcal/day. With such increased caloric intake, there is an increased load on metabolic pathways, in particular glucose metabolism. Such metabolism requires micronutrients as enzyme co-factors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 130 publications
(168 reference statements)
1
46
0
Order By: Relevance
“…To obtain insight into roles of unreported adipose-specific genes in adipose tissue, functional annotations of the genes and information from literature describing their potential functions in other tissues and results from analysis of GSE data were summarized (Table 1). Among these adipose-specific genes, CSN1S1 is involved in immune/inflammatory responses 30 , SLC19A3 is responsible for thiamine transport and subsequent energy production 31 , and LVRN ( AQPEP ) is a member of the aminopeptidase family that catalyzes peptide catabolic processes 32 . Of particular interest, GSE data (GSE9624 and GSE12050) showed that SLC19A3 and CSN1S1 genes were expressed significantly higher in omental and subcutaneous adipose tissue, respectively, of an obese population than a lean population (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain insight into roles of unreported adipose-specific genes in adipose tissue, functional annotations of the genes and information from literature describing their potential functions in other tissues and results from analysis of GSE data were summarized (Table 1). Among these adipose-specific genes, CSN1S1 is involved in immune/inflammatory responses 30 , SLC19A3 is responsible for thiamine transport and subsequent energy production 31 , and LVRN ( AQPEP ) is a member of the aminopeptidase family that catalyzes peptide catabolic processes 32 . Of particular interest, GSE data (GSE9624 and GSE12050) showed that SLC19A3 and CSN1S1 genes were expressed significantly higher in omental and subcutaneous adipose tissue, respectively, of an obese population than a lean population (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thiamin is known for its role in catalyzing glucose metabolism [44]. Studies have shown that the lower intakes of thiamin are associated with a higher frequency of obesity and overweight [44,45]. Therefore, the lower percentage of obese and overweight adults in the balanced intakes of grain might be explained by the balanced intake of carbohydrates, energy, and thiamin in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lower percentage of obese and overweight adults in the balanced intakes of grain might be explained by the balanced intake of carbohydrates, energy, and thiamin in this group. The importance of thiamin in the metabolism of glucose, and consequently its association with obesity, is indicated in a systematic review [45]. However, a study indicated that the prevalence of diabetes and obesity in the U.S were associated with higher intakes from the vitamin B family, such as niacin and thiamin, during the last 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…In general, thiamine deficiency occurs in 15.5 to 29% of patients with obesity . Thiamine testing may be considered pre‐operatively in light of reports describing relatively high prevalence rates of thiamine deficiency in patients awaiting bariatric surgery (16 to 47%, depending on ethnicity), early onset Wernicke encephalopathy (WE) 2 weeks after bariatric surgery instead of the more usual 3 months, and the potential prevention of WE with diligent pre‐operative thiamine replacement protocols . In a single institution, a retrospective observational study of 400 patients undergoing bariatric surgery showed that 16.5% had clinical thiamine deficiency preoperatively (consistent symptomatology and either low biochemical levels or significant improvement with thiamine supplementation) and 18% after RYGB .…”
Section: Executive Summarymentioning
confidence: 99%